A study on the formulation of the Philippine human rights plan (1996-2000) a policy paper - Castillo, Marivic B. (2003)
The basic problem that this policy issue paper wants to discuss and address is the weaknesses and limitations in the formulation process of the Philippine Human Rights Plan (1996-2000). The policy paper has two main objectives namely : Review the PHRP formulation process and generate lessons for the next human rights plan. Using secondary data and a number of key informant interviews, the process of formulating the Plan was examined and analyzed. Using the experiences of the first PHRP as a context, the study generated lessons which can be used in the preparation of the next PHRP. After more than five years of implementation, there is a strong perception to proceed to the next phase of the Plan. However, this second phase is characterized by the challenge of doing it the "better way" to address the concerns and difficulties in the first plan. The study is limited to the examination of the formulation process. This stems from the hypothesis that many of the issues encountered during the PLan implementation was caused by the manner the Plan was developed.
A policy paper submitted in partial fulfillment of the course requirement of PA 247 (Policy Paper)
"October 2003."
Keywords: Human rights -- Government policy -- Philippines